1996
DOI: 10.1017/s0022215100133122
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous diffuse neurofibroma of the neck: a case report

Abstract: A case of a rare and unusual variant of neurofibroma, diffuse neurofibroma (paraneurofibroma), in a young patient is presented. The clinical, radiological and histopathological features of this case are reported. The magnetic resonance imaging (MRI) features of the diffuse neurofibroma are comparable with those described in other neurofibromas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
1
11
1
Order By: Relevance
“…There is intense enhancement on T 1 W post-contrast administration. 3 , 4 , 10 These findings correlate well with the MR findings in this case. On imaging with ultrasound and MR, localized neurofibromas are circumscribed soft tissue masses unlike diffuse neurofibromas that are less well-defined and more infiltrative.…”
Section: Outcome/follow-up/discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There is intense enhancement on T 1 W post-contrast administration. 3 , 4 , 10 These findings correlate well with the MR findings in this case. On imaging with ultrasound and MR, localized neurofibromas are circumscribed soft tissue masses unlike diffuse neurofibromas that are less well-defined and more infiltrative.…”
Section: Outcome/follow-up/discussionsupporting
confidence: 89%
“… 1–11 Although earlier literature suggested diffuse neurofibromas to be most frequently found in the head and neck region, more recently Hassel et al reported that the trunk and extremities are the commonest locations. 3 , 12 There have been reported retroperitoneal location and associations with diffuse cystic lung disease. 13 …”
Section: Outcome/follow-up/discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the rich vascular supply, preoperative angiogram and intra-arterial embolization may be helpful in reducing the risk of hemorrhage. 6,7 Given the infiltrative growth pattern and multicentricity of the tumor, clinical recurrences are common, even after complete surgical excision. Because of the recurrence potential, malignant transformation and NF development possibility, yearly follow-up is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic MR pattern of a diffuse neurofibroma, as seen on T1-weighted imaging, is linear or reticular strands of intermediate signal intensity in the subcutaneous fat, which indicates infiltration of the tumor components of neurofibromatous tissue, interposed collagen, and ectatic vessels [2,3,5]. T2-weighted imaging shows high signal intensity of the linear and reticular strands of the tumor elements that contain neurofibromatous tissue and ectatic vessels, but the interposed collagen remains intermediate to low signal intensity.…”
Section: On the Ajr Viewbox Diffuse Neurofibroma Of The Arm: Mr Charamentioning
confidence: 99%